Serum glycoprotein non-metastatic melanoma protein B (GPNMB) level as a potential biomarker for diabetes mellitus-related cataract: A cross-sectional study - Huo, Da; Liu, Yuan-Yuan; Zhang, Chi; Zeng, Lv-Tao; Fan, Guo-Qing; Zhang, Li-Qun; Pang, Jing; Wang, Yao; Shen, Tao; Li, Xue-Fei; Li, Chuan-Bao; Zhang, Tie-Mei; et al. (Frontiers in Endocrinology, 2023)
Background: Diabetes mellitus (DM), a metabolic disease that has attracted significant research and clinical attention over the years, can affect the eye structure and induce cataract in patients diagnosed with DM. Recent studies have indicated the relationship between glycoprotein non-metastatic melanoma protein B (GPNMB) and DM and DM-related renal dysfunction. However, the role of circulating GPNMB in DM-associated cataract is still unknown. In this study, we explored the potential of serum GPNMB as a biomarker for DM and DM-associated cataract. Methods: A total of 406 subjects were enrolled, including 60 and 346 subjects with and without DM, respectively. The presence of cataract was evaluated and serum GPNMB levels were measured using a commercial enzyme-linked immunosorbent assay kit. Results: Serum GPNMB levels were higher in diabetic individuals and subjects with cataract than in those without DM or cataract. Subjects in the highest GPNMB tertile group were more likely to have metabolic disorder, cataract, and DM. Receiver operating characteristic (ROC) curve analysis also indicated that GPNMB could be used to diagnose DM and cataract. Multivariable logistic regression analysis illustrated that GPNMB levels were independently associated with DM and cataract. DM was also found to be an independent risk factor for cataract. Further surveys revealed the combination of serum GPNMB levels and presence of DM was associated with a more precise identification of cataract than either factor alone. Conclusions: Increased circulating GPNMB levels are associated with DM and cataract and can be used as a biomarker of DM-associated cataract.